2012
DOI: 10.1007/s10761-012-0182-1
|View full text |Cite
|
Sign up to set email alerts
|

Remembering Places Never Visited: Connections and Context in Imagined and Imaginary Landscapes

Abstract: Despite the vast research on landscape and landscape archaeology conducted over the past decade little attention has been given to the role of memory and imagination in people's engagement with their ancestral homelands, "country" or other meaningful landscape. An analysis of a range of case studies, both historical and contemporary reveal that people often feel great attachment to and desire to engage with lands that they may have never visited or have little empirical evidence for attachment. Further complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 14 publications
2
18
0
1
Order By: Relevance
“…To our knowledge, this is the first study to provide empirical evidence to the concept of place attachment toward destinations not previously experienced, developed on the basis of media exposure. More specifically, this research supports the assertion that place attachment is stimulated by narratives (Low 1992; Russell 2012), which imbue imaginary places with emotional and symbolic meaning. Second, this research draws on symbolic interactionism theory, the concepts of parasocial interaction (Horton and Wohl 1956) and vicarious experience (Tannenbaum 1980) from media studies to explain place attachment and tourist decision-making behavior (intention to visit).…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…To our knowledge, this is the first study to provide empirical evidence to the concept of place attachment toward destinations not previously experienced, developed on the basis of media exposure. More specifically, this research supports the assertion that place attachment is stimulated by narratives (Low 1992; Russell 2012), which imbue imaginary places with emotional and symbolic meaning. Second, this research draws on symbolic interactionism theory, the concepts of parasocial interaction (Horton and Wohl 1956) and vicarious experience (Tannenbaum 1980) from media studies to explain place attachment and tourist decision-making behavior (intention to visit).…”
Section: Introductionsupporting
confidence: 81%
“…Advancing current knowledge on place attachment, the study found empirical support to the notion that people can develop emotional connection to a place based on narrative links (e.g., Droseltis and Vignoles 2010; Farnum, Hall, and Kruger 2005; Low 1992; Russell 2012). The majority of prior research argues that a long-term direct interaction is a necessary condition for a person–place bonding to arise (Anton and Lawrence 2016; Beckley et al 2007; Kyle, Mowen, and Tarrant 2004).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Vista como um lugar ancestral ou mítico, em virtude dessa dimensão simbólica uma cachoeira pode integrar o imaginário de uma população, mesmo que seja esporadicamente -ou mesmo nunca -visitada (Russell, 2012). Assim, os vestígios antigos que se acumulam sedimentados no entorno das cachoeiras, os quais permitem caracterizá-la como paisagem histórica e arqueológica, acabam por propiciar o substrato às narrativas históricas elaboradas por esses grupos (Sammark;Semple, 2010) e por nós mesmos.…”
Section: As Cachoeiras Como Lugares Significativos E Persistentesunclassified
“…Our contention that landscape loss is a process more akin to dis-incorporation and transformation than annihilation draws on these assertions: Metolong’s inundation will not obliterate identities rooted in memory and place, but will re-locate and re-figure them; the paradox is that this will occur without demographic resettlement. Similar to the ways in which diasporic communities often identify and empathise with unseen or imagined places (Basu, 2005; Lilley, 2006; Russell, 2012), flooding the Phuthiatsana will force residents to re-locate their sense of place while physically staying put. The construction of value in features ‘surviving’ landscape loss becomes significant below.…”
Section: Theories For a Drowning Landscapementioning
confidence: 99%